The Andean Tribunal of Justice and its Interlocutors - Laurence Hefler and Karen Alter (My University, 2016)
In the European Union, national courts have been key intermediaries in helping to bolster and expand the authority of the European Court of Justice through its preliminary reference mechanism. This article analyzes the role of national judges in the Andean Community, a regional legal system whose judicial institution - the Andean Tribunal of Justice (ATJ) - was modeled directly on its European predecessor. Our analysis is based on an original coding of every publically available national court referral to the ATJ from 1987 to 2007 and interviews with over forty participants in the Andean legal system. We find that the relationship between the ATJ and national judges differs significantly from the relationship between the ECJ and its domestic judicial colleagues. As in Europe, references from national judges account for the vast majority of cases on the ATJ's docket. But unlike in Europe, national courts are mostly passive intermediaries. Our coding reveals that national judges do not pose provocative questions to the ATJ, and that there is significant cross-national variation in referral patterns. Interviews corroborate what the data suggests: national judges have a circumscribed understanding of what Andean law requires of them. More than 90% of references involve technical issues of Andean intellectual property (IP) law and the registration decisions of domestic IP administrative agencies. National judges have embraced the ATJ's active role in IP disputes because of the support of these agencies, which seek the Tribunal's guidance to interpret vague areas of Andean law. Outside the area of IP, national judges are far more reluctant, contributing to the limited penetration of Andean law into national legal orders. We conclude by comparing the role of national judges in Europe to their role in the Andean context, extracting broader insights about the role of national judges in building international rules of law.